A Juridical Analysis Of Legal Protection For Doctors And Patients In Medical Aesthetic Services (A Review Under Law No. 17 Of 2023 On Health And Law No. 8 Of 1999 On Consumer Protection) - Frien Refla Syarif; Marice Simarmata (Fakultas Hukum Dehasen, 2026)
The field of medical aesthetics has experienced rapid growth in recent years, in line with the increasing public awareness of the importance of appearance, skin care, and technological advancements in aesthetic medicine. However, behind this progress lie several legal issues that require serious attention, including unauthorized medical practice, alleged malpractice, and the inadequate legal protection afforded to both patients and medical practitioners. This study aims to examine the forms of legal protection available to doctors and patients in the practice of medical aesthetic services, with reference to Law Number 17 of 2023 on Health and Law Number 8 of 1999 on Consumer Protection. The research employs a normative juridical (doctrinal) method using a statute approach and a conceptual approach. The analysis is carried out qualitatively by examining primary, secondary, and tertiary legal materials. These two legal instruments serve as the primary foundation for ensuring legal protection for both parties; however, their implementation still requires derivative regulations and clearer enforcement mechanisms to strengthen their effectiveness. The government, the Professional Discipline Council, and the public are expected to play an active role in establishing an aesthetic medical service system that is safe, ethical, and equitable. Reforms to Indonesia’s health law framework should be directed toward an integrative and humanistic model of legal protection—one that not only safeguards medical practitioners from potential criminalization but also ensures patient safety and the protection of patients’ rights as consumers of aesthetic medical services. This study is expected to provide new perspectives and contribute to the growing body of literature in the field of health law in Indonesia.